1993
DOI: 10.1176/ajp.150.11.1618
|View full text |Cite
|
Sign up to set email alerts
|

The DST as a predictor of outcome in depression: a meta-analysis

Saulo C.M. Ribeiro,
Rajiv Tandon,
Leon Grunhaus
et al.

Abstract: Baseline DST results may be devoid of prognostic value, but posttreatment nonsuppression of cortisol on the DST is strongly associated with poor outcome. Persistent nonsuppression may reflect a partially treated index episode or identify sicker patients who are unresponsive to treatment. The findings reiterate the importance of studying biological measures in relation to multiple validators of psychiatric illness beyond cross-sectional diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(41 citation statements)
references
References 120 publications
1
39
0
Order By: Relevance
“…The significance of HPA-axis modulation in depression is underscored by reports that successful antidepressant treatment is associated with resolution of impairment in HPA-axis negative feedback. 38, 39 Our data show that the ability of animals to recover from the SC-induced submissive phenotype is critically dependent on intact neurogenesis. Given previous evidence that the HPA-axis is altered by EE exposure and that neurogenesis modulates the HPA-axis stress response, it is plausible that the antidepressant effects of EE in behavioral recovery from SC are mediated via regulation of the HPA axis by neurogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…The significance of HPA-axis modulation in depression is underscored by reports that successful antidepressant treatment is associated with resolution of impairment in HPA-axis negative feedback. 38, 39 Our data show that the ability of animals to recover from the SC-induced submissive phenotype is critically dependent on intact neurogenesis. Given previous evidence that the HPA-axis is altered by EE exposure and that neurogenesis modulates the HPA-axis stress response, it is plausible that the antidepressant effects of EE in behavioral recovery from SC are mediated via regulation of the HPA axis by neurogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…Some potential markers include abnormalities of the hypothalamic-pituitary-adrenal (HPA) axis as measured by nonsuppression in the dexamethasone suppression test (DST), impaired lymphocyte glucocorticoid sensitivity and abnormal sleep EEG patterns [114]. While the baseline DST does not predict antidepressant treatment response or outcome after hospital discharge, research has suggested that the DST tends to return to normal as a result of antidepressant treatment [114, 115]or cognitive behavior therapy [116]. Abnormal DST results that persist after treatment and EEG sleep abnormalities have been associated with poor prognosis and higher relapse rates [114, 117].…”
Section: Belief No 3: Antidepressants Are Necessary To Redress a Chementioning
confidence: 99%
“…Hyperactivity of the HPA axis has been observed in patients with major depressive disorder and with poorer antidepressant outcome [8,9]. Moreover, elevated cortisol levels and no suppression of cortisol secretion after dexamethasone suppression test (DST) have been associated with worse antidepressant treatment outcome, relating the HPA axis dysregulation to the response [10]. This suggests that patients resistant to antidepressant treatment may represent a biologically distinct group [8,9].…”
Section: Introductionmentioning
confidence: 99%